The concepts of big data applied in personal knowledge management. Issue 1 (13th February 2017) - Liu, Che-Hung; Wang, Jen Sheng; Lin, Ching-Wei
Abstract : Purpose: The purpose of this paper is to demonstrate the applications of big data in personal knowledge management (PKM). Design/methodology/approach: Five conventional knowledge management dimensions, namely, the value of data, data collection, data storage, data application and data presentation, were applied for integrating big data in the context of PKM. Findings: This study concludes that time management, computer usage efficiency management, mobile device usage behavior management, health management and browser surfing management are areas where big data can be applied to PKM. Originality/value: While the literature discusses PKM without considering the impact of big data, this paper aims to extend existing knowledge by demonstrating the application of big data in PKM.